A Support Program For Mothers As Caregivers Of Children With Disabilities In Indonesia - Aditya Kurniawan; Nanda Wulandari; Reny Yuniasanti (International Journal Of Community Service, 2022)
As primary caregivers of children with disabilities, mothers in Javanese society play a significant role in nurturing a child's independence. However, the families often blame mothers when giving birth to children with disabilities. Preliminary data showed that mothers with children with disabilities tend to have a high sense of guilt upon their children's conditions and lack knowledge of supporting child growth. The mothers also have lack support from their spouses and families. These situations make mothers experience mental and physical exhaustion, chronic stress, irritability, and lack of confidence, which leads to ineffective parenting strategies. The program's purpose is to equip caregivers with knowledge of stress management and effective parenting strategies for children with disabilities.